Etnobotani Tumbuhan Obat Tradisional Masyarakat Suku Dayak Banyadu di Desa Teriak Kabupaten Bengkayang - Irma Elisetana; Masnur Turnip; Irwan Lovadi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The Dayak Banyadu tribe is one of the Dayak tribes in Kalimantan. This tribe inhabits several areas in Bengkayang Regency, including in the Teriak District area. The Dayak Banyadu people are known to still use plants as traditional medicine. The purpose of this study was to determine the types of medicinal plants, diseases that can be cured, as well as the use and processing of plants as traditional medicine among the Dayak Banyadu people. This type of research is descriptive quantitative. The research was conducted using a semi-structured interview technique guided by a list of questions or a questionnaire. The population of this study was the Dayak Banyadu people living in Teriak Village, Bengkayang Regency, which was determined by the snowball sampling method. The number of respondents was 14 people consisting of traditional leaders, village shamans and people who had knowledge about medicinal plants. The Dayak Banyadu tribe in Teriak Village has the potential for medicinal plants with reference to medicinal plant cultivation. The Dayak Banyadu people utilize 50 species from 30 families. The most numerous families are Asteraceae (5 species) and Zingiberaceae (4 species). The most widely used part of medicinal plants is the leaves (58.9%). Processing method that is most often used is pounded (44.1%). The way to use it most often is sticking (43.1%). The location where most medicinal plants were collected was in the yard of the house (38%). The results of data calculations obtained Fidelity Level (FL) values (100%) of 37 species used to treat diseases. The highest Informant Agreement Factor (FKI) score (1,000) was for 3 disease categories, namely hyperglycemia, hyperlipidemia and uterine disorders.